2021
DOI: 10.33794/qjas.2021.168286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Predatory Efficiency of Orius Albidipennis Reuter for Two Prey Species Myzus Persicae (Sulzer) and Thrips Tabaci Lind. on The Carrot Plant in Laboratory

Abstract: The study aimed to investigate the effect of different densities of M.persicae and T. tabaci on the predatory ability of the predator O. albidipennis and determine the preference for one of the two prey, in addition to assessing the in vitro predator's efficiency in reducing the number of aphids on the carrot plant. The results indicated that the rates of predated adult and nymph thrips were significantly higher than that of predated aphids. The highest rate of predation for nymphs and adults thrips was 33.2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In fact, Mahendran and Radhakrishnan [ 37 ] observed that the commercialized Aeolothripidae predator Franklinothrips vespiformis larvae are able to prey on 12 Scirtothrips bispinosus (a Thripidae harmful for tea plantations) adults within 24 h. In our experiment, the prey ( T. tabaci adults) were administrated sequentially (three prey every three hours) in order to keep the prey/predator rate quite constant during the experiment. However, Khamis and Jabbar [ 38 ] and El-Sheikh et al [ 39 ] observed that the number of prey ( T. tabaci adults) killed by Orius albipennis was significantly correlated with the prey density varying from 10 to 25 prey per day for prey densities from 10 to 60 per predator. This indicates that under field working conditions with higher prey densities, A. intermedius could increase its predatory efficacy and be a very effective predator for the control of T. tabaci , with predation rates in line with other predators already commercialized ( F. vespiformis , Orius sp., and predatory mites).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Mahendran and Radhakrishnan [ 37 ] observed that the commercialized Aeolothripidae predator Franklinothrips vespiformis larvae are able to prey on 12 Scirtothrips bispinosus (a Thripidae harmful for tea plantations) adults within 24 h. In our experiment, the prey ( T. tabaci adults) were administrated sequentially (three prey every three hours) in order to keep the prey/predator rate quite constant during the experiment. However, Khamis and Jabbar [ 38 ] and El-Sheikh et al [ 39 ] observed that the number of prey ( T. tabaci adults) killed by Orius albipennis was significantly correlated with the prey density varying from 10 to 25 prey per day for prey densities from 10 to 60 per predator. This indicates that under field working conditions with higher prey densities, A. intermedius could increase its predatory efficacy and be a very effective predator for the control of T. tabaci , with predation rates in line with other predators already commercialized ( F. vespiformis , Orius sp., and predatory mites).…”
Section: Discussionmentioning
confidence: 99%